IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI SMP NEGERI 1 CILIMUS - Nana Charcinah; Jaja Wilsa (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the implementation of the School Literacy Movement (GLS) program at SMP Negeri 1 Cilimus-Kuningan. This type of research uses descriptive qualitative. Methods of data collection using interviews, observation, and documentation. The results of the study show that the School Literacy Movement has been well implemented. The School Literacy Movement is carried out by giving students 15 minutes before class to read various types of reading from books, magazines, newspapers, or the internet. After that, students were randomly asked to report their reading results in front of the class. This effort was made by the school in supporting the School Literacy Movement. By implementing the School Literacy Movement, students' interest in reading will increase.